Políticas para a educação a distância: o sistema Universidade Aberta do Brasil - Antunes, Neuza Maria Barbosa de Oliveira (2011)
Public policies have been widely discussed in academic circles, especially those that permeate the field of education. This study presents an analysis of specific policies that have guided the expansion of distance education in Brazil, focusing on an analysis of the constitution and deployment of the Open University of Brazil, who now plays the role of management in the context of public participation in the form of distance education. The labor organization is stretched by a historical survey of Brazilian education in which we contemplate the beginnings of Distance Education, a construction of the foundations law governing this type since 1996 and a broad description of the main policy in this area, the University System Brazil Open. During the study it was observed that the actions that made all the necessary apparatus for the expansion of educational services in the form of distance education is based on policy positions and always in accordance with the views of international bodies suggested as a mechanism to address emergency the national indices of education the use of new information technologies and communication. It says that using this type of education is in line with the directions that emphasize liberal conception of state minimum for social policies and the economic environment, the large-scale production to reduce costs, including the actions of education. It also analyzes some of the work of the Open University of Brazil in the context of Brazilian higher education and how policies were being forwarded in this sector for the Open University of Brazil came on the scene and began to compose the Brazilian education, by expanding the role of modality Distance education in the country.